A clinical study of Stevens-Johnson syndrome and toxic epidermal necrolysis in a tertiary centre, South India - S., Rahima; E. N., Abdul Latheef; K., Pavithran; P. M., Saleem (International Journal of Research in Dermatology, 2017)
Background: Stevens Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are considered as the severest end of spectrum of erythema multiforme. Various etiologies like infections, drugs and malignancies have been proposed. The aim of the present study was to know the incidence, common causes, clinical course of SJS and TEN and to estimate the morbidity and mortality. Methods: A 2 year study of patients presenting with SJS and TEN was carried out. A detailed examination to know the cutaneous and mucosal involvement was done. Biopsy was done in 3 patients. Results: There were fifty patients of SJS-TEN spectrum. Of which 31 were SJS, 3 had SJS-TEN overlap and 16 had TEN. Anticonvulsants were implicated in causing these reactions in 24 patients (48%) with carbamazepine being the most common i.e. in 16 patients (32%). Sparing of pressure areas like the strap area of brassier and waist was noticed in two patients (4%). The most common complication was due to eye involvement seen in 20 patients (40%). 46 patients were treated with steroids and of the remaining, 3 were children and one was HIV positive. Only three patients with TEN (6%) died. Conclusions: To conclude, TEN was less common than SJS, had more sequelae and more mortality compared to SJS.